CD16+ Monocyte Subset Was Enriched and Functionally Exacerbated in Driving T-Cell Activation and B-Cell Response in Systemic Lupus Erythematosus - Zhu, Huaqun; Hu, Fanlei; Sun, Xiaolin; Zhang, Xiaoying; Zhu, Lei; Liu, Xu; Li, Xue; Xu, Liling; Shi, Lianjie; Gan, Yuzhou; Su, Yin (Frontiers in Immunology, 2016)
Background: The roles that CD16+ monocyte subset plays in T-cell activation and B-cell response have not been well studied in systemic lupus erythematosus (SLE). Objective: The present study aimed to investigate the distribution of CD16+ monocyte subsets in SLE and explore their possible roles in T-cell activation and B-cell differentiation. Methods: The frequencies of monocyte subsets in the peripheral blood of healthy controls (HCs) and patients with SLE were determined by flow cytometry. Monocyte subsets were sorted and co-cultured with CD4+ T cells and CD19+ B cells. Then, T and B cells were collected for different subset detection, while the supernatants were collected for immunoglobulin G (IgG), IgA, and IgM or interferon (IFN)-γ and interleukin (IL)-17A detection by enzyme-linked immunosorbent assay. Results: Our results showed that CD16+ monocytes exhibited a pro-inflammatory phenotype with elevated CD80, CD86, HLA-DR, and CX3CR1 expression on the cell surface. It’s further demonstrated that CD16+ monocytes from patients and HCs shared different cell-surface marker profiles. The CD16+ subset was enriched in SLE and had an exacerbated capacity to promote CD4+ T cell polarization into a Th17 phenotype. Also, CD16+ monocytes had enhanced impacts on CD19+ B cells to differentiate into plasma B cells and regulatory B cells with more Ig production. Conclusions: This study demonstrated that CD16+ monocytes, characterized by different cell-surface marker profiles, were enriched and played a critical role in driving the pathogenic T- and B-cell responses in patients with SLE.